Curriculum Studies in China Intellectual Histories, Present Circumstances - Pinar, William F.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Scholars from three continents collaborate to create a truly global understanding of curriculum in the world's most populous country. This book discusses major topics in curriculum studies in China and shows how Chinese scholars understand their field's history, circumstances, and place in a globalized world.
Keywords: Science; Science; Science, general